2010
DOI: 10.1002/bjs.7124
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic action of oncolytic herpes simplex virus and radiotherapy in pancreatic cancer cell lines

Abstract: The synergistic oncolytic actions of HSV and radiotherapy observed in pancreatic cancer cell lines encourage further testing of this multimodality treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…We found that radiotherapy and HSV produced the synergistic oncolytic activity against pancreatic cancer cell lines. However, the radiotherapy at different doses had no impact on HSV viral replication in our study [5]. Other studies also showed that synergistic cytotoxicity between HSV-1 and chemotherapy was not related to alteration in viral replication [67,68].…”
Section: Hsv Combined With Conventional Therapiescontrasting
confidence: 58%
See 1 more Smart Citation
“…We found that radiotherapy and HSV produced the synergistic oncolytic activity against pancreatic cancer cell lines. However, the radiotherapy at different doses had no impact on HSV viral replication in our study [5]. Other studies also showed that synergistic cytotoxicity between HSV-1 and chemotherapy was not related to alteration in viral replication [67,68].…”
Section: Hsv Combined With Conventional Therapiescontrasting
confidence: 58%
“…As the first oncolytic viruses to be introduced in fighting against cancer, HSV are easily manipulated and can be inserted transgene. Moreover, previous work from our studies and others has shown that HSV combined with radiotherapies or chemotherapies produce synergistic action [5,6]. The HSV used as oncolytic agents offer some advantages: (i) HSV infects most tumor cells types and replicates rapidly in infected cells; (ii) HSV virions have the ability of viral penetration within tumor; (iii) HSV with a large genome is easily manipulated and can be inserted multiple transgenes; (iv) HSV replication can be shut off with anti-HSV drug if required [7][8][9][10].…”
mentioning
confidence: 51%
“…Radiation in combination with HSV-1 mutants has demonstrated enhanced kill in tumor models (35)(36)(37)(38)(39). Moreover, there are indications that the interaction between HSV-1 and radiation is synergistic, possibly because of increased viral replication and improved dissemination of the virus within tumors (36,39).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that HSV 1 has a tendency to reduce apoptosis through several mechanisms, such as the PKR pathway and the US3 arm of the viral genome. 53 Some oncolytic herpes viruses reduce apoptosis; 45,46,54 whereas others enhance apoptosis. 43,44,47 The effect of oncolytic herpes viruses on apoptosis is strain specific and depends on the underlying genetic variation.…”
Section: X400 X400mentioning
confidence: 99%